2021
DOI: 10.3390/educsci11060275
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Learning in Pre-Service Teacher Education: Perceived Usefulness of AR Technology in Primary Education

Abstract: Mobile learning is a resource that can enhance the teaching-learning process of students and improve the training of future teachers. Specifically, augmented reality (AR) technology allows for immersive and experiential learning without the need to leave the classroom. The purposes of this paper were to apply AR technology in the training of future Primary Education teachers and to analyze the perceived usefulness of AR in the classroom by future teachers. A quantitative approach was used based on a design wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Comparatively, this study found that the students thought that the use of m-learning and CAPE framework was an effective and smart approach to English learning, as the gamebased quizzes, group discussions and classroom activities were perceived to produce a significant change in their receptive skills. This finding is in tandem with notable studies on m-learning which recommend m-learning for preservice teacher education, higher education and primary education with models of good teaching practice and is perceived as effective when integrated with artificial intelligence (Romero-Rodr ıguez et al, 2020b;G omez-Garc ıa et al, 2021). This result unveils the suppositions from studies on LDfs that contextual inputs in form of activities play a significant role in language teaching (Anderson, 2017a).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Comparatively, this study found that the students thought that the use of m-learning and CAPE framework was an effective and smart approach to English learning, as the gamebased quizzes, group discussions and classroom activities were perceived to produce a significant change in their receptive skills. This finding is in tandem with notable studies on m-learning which recommend m-learning for preservice teacher education, higher education and primary education with models of good teaching practice and is perceived as effective when integrated with artificial intelligence (Romero-Rodr ıguez et al, 2020b;G omez-Garc ıa et al, 2021). This result unveils the suppositions from studies on LDfs that contextual inputs in form of activities play a significant role in language teaching (Anderson, 2017a).…”
Section: Discussionsupporting
confidence: 70%
“…This finding is in tandem with notable studies on m-learning which recommend m-learning for preservice teacher education, higher education and primary education with models of good teaching practice and is perceived as effective when integrated with artificial intelligence (Romero-Rodríguez et al. , 2020b; Gómez-García et al. , 2021).…”
Section: Discussionsupporting
confidence: 69%
“…A study showed that the AR experiment promoted only a slight increase in student motivation Gomez-Garcia et al (2021). However, no significant differences were found between the control and experimental groups.…”
Section: Impact Of Augmented Reality Technology On Teaching Effective...mentioning
confidence: 97%
“…With respect to AR books, in particular, several research studies focused on the use of AR books by university students [31]- [35] to examine their cognitive load, motivation, and attitudes [33], [34] to examine their learning in Biology [35], and to examine their motivation and improvement in academic performance [31], [32]. The majority of previous studies measured attitudes and behaviors, such as acceptance, adoption, and confidence towards AR books targeting adults, for example, university students [33] or future teachers [6], [36] or parents [37]- [39]. The studies that targeted parents examined their interaction with young children while reading AR books [37], [39].…”
Section: Related Workmentioning
confidence: 99%
“…Examples of innovative student-centered learning environments include web-based interactive learning environments [2], [3], gamified applications for mobile devices [4], applications employing the Internet of Things [5], immersive virtual reality applications, and augmented reality (AR) applications. These emerging technologies allow for immersive and experiential learning within a classroom [6] while at the same time being motivational for learners to use.…”
Section: Introductionmentioning
confidence: 99%